2016
DOI: 10.5897/ajbm2016.8153
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between institutional quality and stock market performance: Evidence from emerging economies

Abstract: The purpose of this study is to provide empirical evidence on the effect of institutional quality on stock market performance. In order to evaluate the effect of institutional quality on stock market performance, Calderon Rossell models have been estimated using generalized method of moment's technique. A panel data of 41 emerging countries for the period 1996 to 2011 is used to estimate the results. The results suggest that institutional quality has a positive and significant influence on stock market perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was concluded that in the case of developed economies stock markets operate under efficient governance and institutional framework to enhance the stock returns and lower level of risk. Results are consistent with ((Winful et al, 2016;Marshall et al, 2017;Eldomiaty et al, 2019) Incorporating the role of control variables in determining the stock market returns in Advanced countries. GDP Deflator, Trade openness, short-term interest rate, and oil price have a significant negative influence on the stock market returns.…”
Section: Ar(1) Ar(2)supporting
confidence: 77%
“…It was concluded that in the case of developed economies stock markets operate under efficient governance and institutional framework to enhance the stock returns and lower level of risk. Results are consistent with ((Winful et al, 2016;Marshall et al, 2017;Eldomiaty et al, 2019) Incorporating the role of control variables in determining the stock market returns in Advanced countries. GDP Deflator, Trade openness, short-term interest rate, and oil price have a significant negative influence on the stock market returns.…”
Section: Ar(1) Ar(2)supporting
confidence: 77%
“…The study used carbon emissions (AirQ) as the air quality variable and GDP (in constant 2015 US$) as the total output variable. Investments made for the transition to renewable energy as green nance (GF) variable, REC and NREC as energy consumption (EC), and institutional quality variable (IQ) were calculated as the average of 5 different indexes calculated by the World Bank ( Winful, Sarpong, & Ntiamoah, 2016). These; include accountability, the role of law, effectiveness of government, quality of regulation, and control of corruption.…”
Section: Datamentioning
confidence: 99%
“…When institutions are strong the financial sector performs well and plays a role in the growth of GDP (Rashid and Intartaglia, 2017). Winful et al, (2016) also concluded in their study that institutional quality plays a positive role in the performance of the stock market. Results support the hypothesis of this study.…”
Section: Resultsmentioning
confidence: 92%